A multi-objective optimization system for mobile gateways selection in vehicular Ad-Hoc networks. (January 2019) - Retal, Sara; Idrissi, Abdellah
Abstract: Vehicular ad-hoc networks provide essential Internet services to users. In consequence, mobile gateways are deployed to guarantee access to the Internet for the entire network. However, the selection of the best gateway taking into account some constraints and trying to reach some high-level objectives is a significant issue in mobile gateways discovery. The number of connected client vehicles must be maximized while a fair load distribution must be performed. For this purpose, we propose a multi-objective optimization system for mobile gateways selection based on two models using different solving strategies allowing the decision maker to choose the adequate solution. The solving approaches are evaluated and compared, and the simulations prove its efficiency compared to that found in the literature. The results show the effectiveness of the system in supporting a decision maker in solving a gateway selection problem and finding a fair solution in case there are no user preferences.